2011
DOI: 10.1093/occmed/kqr001
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and chronic disease: the epidemiological evidence

Abstract: Background Shift work, including night work, has been hypothesized to increase the risk of chronic diseases, including cancer, cardiovascular disease (CVD), metabolic syndrome and diabetes. Recent reviews of evidence relating to these hypotheses have focussed on specific diseases or potential mechanisms, but no general summary of the current data on shift work and chronic disease has been published.Methods Systematic and critical reviews and recent original studies indexed in PubMed prior to 31 December 2009 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
372
1
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(403 citation statements)
references
References 75 publications
10
372
1
20
Order By: Relevance
“…Although there have been few studies on a relationship between shift work and dental diseases, a relationship between shift work and systemic diseases such as cancer, cardiovascular disease and gastrointestinal disease have been discussed [22,23]. Knutsson reported that the possibility of affecting shift work on behavioural changes and stress because of shift work could cause disturbed sociotemporal patterns [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been few studies on a relationship between shift work and dental diseases, a relationship between shift work and systemic diseases such as cancer, cardiovascular disease and gastrointestinal disease have been discussed [22,23]. Knutsson reported that the possibility of affecting shift work on behavioural changes and stress because of shift work could cause disturbed sociotemporal patterns [24].…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs études ont identifié une association des polymorphismes dans les gènes de l'horloge (Clock, Bmal1, Cry, Rev-erba) à l'obésité, l'hyperglycémie et le diabète de type 2 [19][20][21][22]. Par ailleurs, plusieurs études attestent de l'augmentation de la survenue de l'obésité et d'un diabète de type 2 chez les travailleurs postés [23]. L'impact des désyn-chronisations plus légères, mais répétées, telles que le décalage social entre les horaires de semaine et ceux du week-end, ou le déficit chronique de sommeil n'a SYNTHÈSE REVUES leur activité, oscille de façon circadienne.…”
Section: Couplage De L'horloge Moléculaire Avec Le Statut Métaboliqueunclassified
“…Shift work is associated with many negative health effects, such as obesity. On the other hand, different and long shift work can endanger the physical and mental health of military personnel (1). Shift work can have various adverse effects on human productivity and quality of work life, thus affecting the physical and * mental health, social security, and family life of individuals (2,3).…”
Section: Introductionmentioning
confidence: 99%